RAD25 (SSL2), the yeast homolog of the human xeroderma pigmentosum group B DNA repair gene, is essential for viability. - Park, E (1992)
Xeroderma pigmentosum (XP) patients are extremely sensitive to ultraviolet (UV) light and suffer from a high incidence of skin cancers, due to a defect in nucleotide excision repair. The disease is genetically heterogeneous, and seven complementation groups, A-G, have been identified. Homologs of human excision repair genes ERCC1, XPDC/ERCC2, and XPAC have been identified in the yeast Saccharomyces cerevisiae. Since no homolog of human XPBC/ERCC3 existed among the known yeast genes, we cloned the yeast homolog by using XPBC cDNA as a hybridization probe. The yeast homolog, RAD25 (SSL2), encodes a protein of 843 amino acids (M(r) 95,356). The RAD25 (SSL2)- and XPBC-encoded proteins share 55% identical and 72% conserved amino acid residues, and the two proteins resemble one another in containing the conserved DNA helicase sequence motifs. A nonsense mutation at codon 799 that deletes the 45 C-terminal amino acid residues in RAD25 (SSL2) confers UV sensitivity. This mutation shows epistasis with genes in the excision repair group, whereas a synergistic increase in UV sensitivity occurs when it is combined with mutations in genes in other DNA repair pathways, indicating that RAD25 (SSL2) functions in excision repair but not in other repair pathways. We also show that RAD25 (SSL2) is an essential gene. A mutation of the Lys392 residue to arginine in the conserved Walker type A nucleotide-binding motif is lethal, suggesting an essential role of the putative RAD25 (SSL2) ATPase/DNA helicase activity in viability.